A keystone avian predator faces elevated energy expenditure in a warming Arctic. Issue 5 (1st April 2023) - Grunst, Melissa L.; Grunst, Andrea S.; Grémillet, David; Kato, Akiko; Bustamante, Paco; Albert, Céline; Brisson‐Curadeau, Émile; Clairbaux, Manon; Cruz‐Flores, Marta; Gentès, Sophie; Grissot, Antoine; Perret, Samuel; et al.
Abstract: Climate change is transforming bioenergetic landscapes, challenging behavioral and physiological coping mechanisms. A critical question involves whether animals can adjust behavioral patterns and energy expenditure to stabilize fitness given reconfiguration of resource bases, or whether limits to plasticity ultimately compromise energy balance. In the Arctic, rapidly warming temperatures are transforming food webs, making Arctic organisms strong models for understanding biological implications of climate change‐related environmental variability. We examined plasticity in the daily energy expenditure (DEE) of an Arctic seabird, the little auk ( Alle alle ) in response to variability in climate change‐sensitive drivers of resource availability, sea surface temperature (SST) and sea ice coverage (SIC), and tested the hypothesis that energetic ceilings and exposure to mercury, an important neurotoxin and endocrine disrupter in marine ecosystems, may limit scope for plasticity. To estimate DEE, we used accelerometer data obtained across years from two colonies exposed to distinct environmental conditions (Ukaleqarteq [UK], East Greenland; Hornsund [HS], Svalbard). We proceeded to model future changes in SST to predict energetic impacts. At UK, high flight costs linked to low SIC and high SST drove DEE from below to above 4 × basal metabolic rate (BMR), a proposed energetic threshold for breeding birds. However, DEE remained below 7 × BMR, an alternative threshold, and did not plateau. Birds at HS experienced higher, relatively invariable SST, and operated above 4 × BMR. Mercury exposure was unrelated to DEE, and fitness remained stable. Thus, plasticity in DEE currently buffers fitness, providing resiliency against climate change. Nevertheless, modeling suggests that continued warming of SST may promote accelerating increases in DEE, which may become unsustainable.